LEVEL OF SOCIAL PHOBIA AMONG FACULTY OF PHYSICAL EDUCATION AND SPORTS SCIENCES STUDENTS AT KIRKUK UNIVERSITY - Ali Najmuldeen Abdulrahman; Hisham Salim Ibrahim; Aya Kamran Abdullah (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The importance of the subject emerges from the fact that students of this college are exposed to repeated public performance situations such as practical presentations, skill tests, and arbitration, which are situations that increase the sensitivity to fear of negative evaluation and affect participation and academic performance. Objectives. This research aims to study the level of social phobia among students of the College of Physical Education and Sports Sciences at the University of Kirkuk, and to reveal the differences in its levels according to the gender variable. Method. Utilizing a descriptive-analytical methodology, data were gathered from prior experimental investigations and performance reports in sports, swimming, and cycling to assess biomechanical interventions. Results. The results showed that the students' level of social phobia was medium to high, with "fear of negative evaluation" representing the most prominent dimension (mean 3.85), followed by anxiety in front of others (3.72), while "social withdrawal" was the lowest (3.41). The results of the t -test also showed statistically significant differences (p = 0.002) between the sexes, as females recorded higher levels of social phobia than males, which is consistent with the psychological literature that confirms its greater prevalence among females due to biological and social factors. The study concluded that social phobia poses a real challenge in the academic sports environment and may negatively impact self-confidence, active participation, and achievement. Conclusion. The study recommended the design of guidance and training programs aimed at reducing social phobia and developing communication skills, with a particular focus on supporting female students. It also recommended adopting educational strategies that provide a supportive environment that mitigates assessment pressures.